The Impact of Leadership Styles of Nurse Managers on Nurses’ Motivation and Turnover Intention Among Jordanian Nurses - Smama'h Y; Eshah NF; Al-Oweidat IA; Rayan A; Nashwan AJ (Dove Medical Press, 2023)
Yasen Smama'h,1 Nidal F Eshah,1 Islam A Al-Oweidat,1 Ahmad Rayan,1 Abdulqadir J Nashwan2 1Faculty of Nursing, Zarqa University, Zarqa, Jordan; 2Department of Nursing, Hamad Medical Corporation (HMC), Doha, QatarCorrespondence: Abdulqadir J Nashwan, Hamad Medical Corporation, P.O. Box 3050, Doha, Qatar, Tel +974 40240487 ; +974 66473549, Email anashwan@hamad.qaAim: The purpose of this study is to examine the relationship between leadership styles of nurse managers, nurses' motivation, and turnover intentions among Jordanian nurses.Design: A descriptive correlational cross-sectional study using a self-administered questionnaire was conducted.Methods: A convenience sampling technique was utilized to select the required .sample A sample of 170 registered nurses working at private hospitals in Jordan was surveyed. Moreover, a questionnaire of Path-Goal Leadership, Multidimensional Work Motivation Scale, and Turnover Intention Scale was used to assess leadership styles of nurse managers, nurses' motivation and turnover intention among the participants. Descriptive and inferential tests were used to ask the research questions.Results: The participants perceived the supportive leadership style as the highest (M = 24.4, SD = 4.66). The mean work motivation among participants was 87.12, and the mean turnover intention was 22.01. Nurses' motivation has a positive correlation with all leadership styles. Years of experience predict the nurses' work motivation. Among the leadership styles; two of them significantly predict nurses' work motivation (supportive style) p < 0.001, and (achievement-oriented style) p < 0.001. Finally, the highest correlation coefficient was noticed between work motivation and achievement-oriented style (r = 0.46, p < 0.001) by moderate positive correlation, and the lowest correlation coefficient was between work motivation and directive style (r = 0.29, p < 0.001), whereas the results revealed that turnover intention was not significantly correlated with any of the leadership styles.Conclusion: The results present a unique theoretical underpinning that highlights the factors that affect nurses' turnover intention. So, these findings could be used as guide for policy makers to establish organizational policies toward satisfying nurses' motivation and quality of life to enhance their retention. Besides, enriching the factors that may enhance nurses' motivation and reduce their turnover intention.Keywords: leadership styles, nursing managers, nurses' motivation, turnover intention